2022
DOI: 10.1155/2022/6974909
|View full text |Cite|
|
Sign up to set email alerts
|

Postoperative Cognitive Behavioral Intervention in Patients with Coronary Heart Disease Based on the Effect of Nursing Process Reengineering

Abstract: With the development of society and economy, patients with coronary heart disease increasingly hope to receive more humanized services after surgery, and the reengineering of the nursing process is precisely based on humanized management. In order to create a nursing intervention that helps in boosting total nursing gains and lowering disasters, the primary element of the nursing business process reengineering is to reintegrate or condense the creative work flow that was fragmented by specialization into a who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%